2018
DOI: 10.1111/1365-2435.13068
|View full text |Cite
|
Sign up to set email alerts
|

Rapid larval development under time stress reduces adult life span through increasing oxidative damage

Abstract: While a trade‐off between larval development and adult life span is key to understand why not all animals develop at their maximum rate and why life histories align along a fast‐slow continuum, it has been rarely studied. More general, the physiological mechanisms underlying life‐history trade‐offs are poorly understood and there is ongoing debate about the mediatory role of oxidative stress. We explicitly investigated the role of oxidative stress in mediating the trade‐off between larval development and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 68 publications
(147 reference statements)
5
41
0
Order By: Relevance
“…The inclusion of oxidative stress parameters is motivated by the recognition of oxidative stress as a mediator of life history trade‐offs (Monaghan et al. ; for damselfly larvae, Janssens and Stoks ) and the suggested integration of sensitivity to oxidative stress as part of the POLS, with high sensitivity associated with a fast pace (Réale et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of oxidative stress parameters is motivated by the recognition of oxidative stress as a mediator of life history trade‐offs (Monaghan et al. ; for damselfly larvae, Janssens and Stoks ) and the suggested integration of sensitivity to oxidative stress as part of the POLS, with high sensitivity associated with a fast pace (Réale et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…We assayed a large number of physiological variables: metabolic rate and traits related to investment in selfmaintenance (antioxidant enzymes, oxidative damage, energy storage, immune function and melanin content). The inclusion of oxidative stress parameters is motivated by the recognition of oxidative stress as a mediator of life history trade-offs (Monaghan et al [2009]; for damselfly larvae, Janssens and Stoks [2018]) and the suggested integration of sensitivity to oxidative stress as part of the POLS, with high sensitivity associated with a fast pace (R eale et al 2010). Melanin is a pigment that fulfils a variety of functions, such as immune defense, cuticular hardening, camouflage, and wound healing (Roulin 2014).…”
Section: Physiological Endpointsmentioning
confidence: 99%
“…However, recent work in vivo on birds (Boonekamp, Bauch, Mulder, & Verhulst, ) suggests that six independent oxidative stress markers are uncorrelated with telomere attrition, calling into question the relative role and effect of reactive molecules for telomere dynamics. These are important observations and suggest incomplete understanding of the causal links between reactive molecules, oxidative stress, telomere attrition and life history evolution (see also Janssens & Stoks, ).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological cost can be expressed in terms of the consumption of energy needed to maintain the upregulated antioxidant defenses, to activate the repair systems, to synthesize endogenous antioxidants (such as GSH) as well as to increase the dietary intake of exogenous antioxidants [15,62]. The required energy can be diverted from other processes and can further affect the animal's fitness [63][64][65][66]. This can be more pronounced in natural conditions under which the animals are potentially limited by the available feeding time, food availability, capacity to process energy, predation and other abiotic and biotic factors.…”
Section: Discussionmentioning
confidence: 99%